Ethyiopatogenic And Clinico-Radiological Issues In Syndrome Of Resorption And Atrophy Of Maxillary Bones - Silvia Mihaela Silvas (Romanian Society of Oral Rehabilitation, 2009)
Complex processes of atrophy and resorption of edentulouse ridges manifested by the gradual disappearance of partial or total alveolar bone, which occur, especially after losing dento-periodontal units, was for years the subject of several studies presented in literature. Although so far no such phenomena have not been fully elucidated, however, it was demonstrated that they are totally different from atrophy and resorption mechanisms governing internal transformations of axial skeleton and apendicular bone. All clinical research and laboratory experiments have established with certainty the evolutionary, cumulative and irreversible processes of those who engage in time-anatomical morphological changes and radiological ones in local and loco-regional system stomatognat. Personal studies correlated with data from literature on ethiopatogeny process of atrophy and resorption of edentulous ridges, revealed a number of primary factors (the overall condition of the body factor, age, genetic factors, hormones, nutritional) and aggravating factors (factors similar to factors of etiology of complete edentation functional factors, iatrogeny, risk factors), which are combined in an infinity of cases, making these two complex, multiple disease entity. Conclusions: The mechanisms of producing atrophy and alveolar bone resorption seem to have unlimited potential, regardless of the degree of mineralization of bone and evolve over several years, leading to serious and irreversible morphological changes of skeletal maxillo-facial bone. Along with many other factors, they are significant for planning and forecasting, when required by a conventional removable prosthetic treatment or implants.